2005
DOI: 10.1093/sleep/28.12.1554
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Reflection for Nasal Airway Measurement in Patients with Obstructive Sleep Apnea-Hypopnea Syndrome

Abstract: CPAP use in patients with smaller nasal passages was lower than in those with larger passages. Objective measurement of nasal dimension may be more reliable than subjective self-report of nasal symptoms in identifying patients with OSAHS who might struggle with CPAP therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 21 publications
1
30
0
2
Order By: Relevance
“…Several studies have identified a decrease in nasal volume, resulting in increased nasal resistance, influences CPAP use. (23–26) Acoustic rhinometry measures of nasal dimensions at baseline and after three months of CPAP use were examined by Li and associates. (23) CPAP use was significantly lower in those with a smaller nasal cross-sectional area, with CPAP adherence related to minimal cross-sectional area of the nasal cavity (r = 0.34; p = 0.008), mean area of the nasal cavity (r = 0.27; p = 0.04), and nasal cavity volume (r = 0.28; p = 0.03).…”
Section: What Factors Influence Cpap Adherence?mentioning
confidence: 99%
“…Several studies have identified a decrease in nasal volume, resulting in increased nasal resistance, influences CPAP use. (23–26) Acoustic rhinometry measures of nasal dimensions at baseline and after three months of CPAP use were examined by Li and associates. (23) CPAP use was significantly lower in those with a smaller nasal cross-sectional area, with CPAP adherence related to minimal cross-sectional area of the nasal cavity (r = 0.34; p = 0.008), mean area of the nasal cavity (r = 0.27; p = 0.04), and nasal cavity volume (r = 0.28; p = 0.03).…”
Section: What Factors Influence Cpap Adherence?mentioning
confidence: 99%
“…16 Moreover, long-term patient adherence is typically established within the fi rst week of CPAP therapy. [17][18][19] Certain factors have already been associated with poor adherence to CPAP therapy: lack of sleep specialist consultation prior to polysomnogram (PSG), 20,21 African American race, 20,22 low socioeconomic status, [23][24][25] reduced nasal airway caliber, 26 and mask leak, 27 to name a few. Social factors, such as living with another person, 28 spousal involvement, 29 and participation in educational support groups 30 are associated with improved CPAP adherence.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
“…Li and associates [8 ] employed acoustic rhinometry to measure the internal dimensions of the airway. Measuring the nasal minimal cross-sectional area, mean area and volume, Li and associates found that CPAP use was significantly lower in those with a smaller nasal cross-sectional area (P ¼ 0.007).…”
Section: Patient Characteristicsmentioning
confidence: 99%